2016
DOI: 10.1111/pedi.12459
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes in youth beyond the first year of type 1 diabetes: Results of the Pediatric Diabetes Consortium (PDC) type 1 diabetes new onset (NeOn) study

Abstract: Objective Current data are limited on the course of type 1 diabetes (T1D) in children and adolescents through the first few years of diabetes. The Pediatric Diabetes Consortium T1D New Onset (NeOn) Study was undertaken to prospectively assess natural history and clinical outcomes in children treated at 7 US diabetes centers from the time of diagnosis. This paper describes clinical outcomes in the T1D NeOn cohort during the first 3 years post-diagnosis. Results 1048 participants (mean age 9.2 years, 49% femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 18 publications
6
35
0
Order By: Relevance
“…Over time, there was a progressive reduction in the number of children and adolescents in PREM, with the lowest rate detected 18 months after disease onset (7%). Similarly to our findings, Cengiz et al observed a sharp decline in PREM rates with increasing duration of disease (from 23% at 12 months down to 7% at 36 months in youth with T1D). These data are likely to reflect the natural history of the PREM phase, during which the surviving β‐cell function initially results in a more optimal metabolic control phase, with the lowest HbA1c detected during the first 6 months after T1D onset .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Over time, there was a progressive reduction in the number of children and adolescents in PREM, with the lowest rate detected 18 months after disease onset (7%). Similarly to our findings, Cengiz et al observed a sharp decline in PREM rates with increasing duration of disease (from 23% at 12 months down to 7% at 36 months in youth with T1D). These data are likely to reflect the natural history of the PREM phase, during which the surviving β‐cell function initially results in a more optimal metabolic control phase, with the lowest HbA1c detected during the first 6 months after T1D onset .…”
Section: Discussionsupporting
confidence: 91%
“…Similarly to our findings, Cengiz et al observed a sharp decline in PREM rates with increasing duration of disease (from 23% at 12 months down to 7% at 36 months in youth with T1D). These data are likely to reflect the natural history of the PREM phase, during which the surviving β‐cell function initially results in a more optimal metabolic control phase, with the lowest HbA1c detected during the first 6 months after T1D onset . However, there is a subsequent functional decline in β‐cells reserve, leading to a progressive deterioration of diabetes control .…”
Section: Discussionsupporting
confidence: 91%
“…Intensive insulin treatment improves glycemic control and reduces the risk for acute and long‐term complications. The use of insulin analogs allows children to improve glycemic control with more flexibility in their daily lives, reducing the risk of nocturnal hypoglycemia and postprandial hyperglycemia compared to human regular and intermediate acting insulins . The current report shows a generally satisfactory reimbursement of all types of insulin in Europe for children with T1D, which illustrates the positive trend in insulin reimbursement in the last decade.…”
Section: Discussionmentioning
confidence: 59%
“…To provide intensive insulin therapy, regular self‐monitoring of glucose is essential for effective diabetes management . A greater frequency of finger prick glucose monitoring improves diabetes control due to better insulin dosing for meals and corrections of out‐of‐target glucose values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation